2000
DOI: 10.1021/jp0006680
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Modes of Double Four-Member Rings of Oxygen-Bridged Silicon and Aluminum Atoms:  A DFT Study

Abstract: The vibrational modes of double four-member ring fragments (D4R) of the general composition [M x ] x +[H8Si8 - x Al x O12] x -, where Si and Al occupy tetrahedral sites, 0≤ x ≤ 4, and M+ is a monovalent charge-compensating cation, are assigned to the framework vibrations of Linde type A (LTA) zeolites. The normal vibrations that arise from configurations with different Si,Al arrangements are calculated by the B3LYP method. Displacement vectors are used to define the ring-opening vibrations as synchronized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Concerning model CG, these values are in good agreement with previous theoretical calculations performed at a similar level of accuracy. 16 The corresponding force constant matrixes have been calculated analytically for the optimal geometries and then diagonalized to obtain the normal vibration modes and frequencies. The characterization of the modes have been performed with use of the symmetry and atomic component analysis implemented in the GAUSSIAN-94 program.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning model CG, these values are in good agreement with previous theoretical calculations performed at a similar level of accuracy. 16 The corresponding force constant matrixes have been calculated analytically for the optimal geometries and then diagonalized to obtain the normal vibration modes and frequencies. The characterization of the modes have been performed with use of the symmetry and atomic component analysis implemented in the GAUSSIAN-94 program.…”
Section: Methodsmentioning
confidence: 99%
“…Infrared spectroscopy is an established method for quantitative studies of chemical reactions occurring inside the pores of zeolites, but vibrational spectroscopy in general (including Raman spectroscopy, infrared spectroscopy and inelastic neutron scattering) has been sparingly used to characterise the framework structure in zeolites. [7][8][9][10][11][12][13][14][15][16] Infrared spectroscopy does not provide sufficiently high spectral resolution to clearly distinguish different zeolite structures through their characteristic vibrational modes, 9,11 while the use of Raman spectroscopy has been limited due to problems of luminescence (in particular in zeolites containing Fe atoms), a low scattering cross section, and many times minor spectroscopic changes upon atomic substitution (e.g. Si -Al).…”
Section: Introductionmentioning
confidence: 99%
“…17 To compensate for these experimental limitations, complementary theoretical calculations have been performed with the aim to elucidate distinct spectral features arising from specific and isolated structural sub-units (such as double 4-membered rings or double 6-membered rings, etc.). 10,12,14,15,18 Group theory has also been invoked to break down the complexity in vibrational spectra of zeolites, which although representing an important contribution also showed that many zeolites of technological and scientific importance are in fact poor candidates for fulllattice dynamics analysis due to the large number of atoms in the Bravais unit cell, and the low space group and site group symmetry. 7 Maroni anticipated already in 1988 7,19 the potential usefulness of polarised Raman spectroscopy on single crystals of zeolites for an otherwise impossible peak assignment.…”
Section: Introductionmentioning
confidence: 99%
“…These vibrations can be both, stretching and bending in nature. As mentioned, in the case of analyzed unit, due to a different number of tetrahedral atoms in 5-membered ring and distinct ring deformation it is hard to talk about typical RO vibrations, however, the characteristic vibrations, which to a large extent fulfilled the criteria of ring vibrations [8,12], of the whole unit can be identified at 524 (Fig. 4a) and 560 cm -1 (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…4, 5). Ideal ring vibrations cause simultaneous and radial (with respect to the ring centre) displacements of atoms from their starting positions without changing the ring symmetry [8,12]. These vibrations can be both, stretching and bending in nature.…”
Section: Resultsmentioning
confidence: 99%